Herramienta informática para la valoración de los factores psicosociales, en la universidad técnica de Cotopaxi. - Cuyo Chiluisa, Jhoana Gabriela (2019)
This project is about the development and implementation of a computer system that helps to monitor the psychosocial factor of occupational medicine of employees, workers and teachers of the Technical University of Cotopaxi (La Matriz). The system is headed to Dr. Richard Pérez, Occupational Doctor of the institution, allowing him to know in a statistical way the levels of stress per each one of them. The software has been made in the programming language, Visual Studio.Net 2015, with a database engine SQL SERVER 2012, each functionality is documented and detailed, for this reason, the Iterative-Incremental model was selected because it is characterized by having phases that helps the development of the systems quickly and efficiently, so that the client can obtain important and usable results from the first iterations. It also helps to carry out in an orderly manner the development of each requirement specified at the beginning of the project by the end user. As a result, a fully functional software is obtained that allows strengthening the Occupational Medical Center, the system has different modules such as: Manage User, Manage Test Questions, Manage System Data, Manage Surveyed, Generate Report by Dimensions, Generate Main Report and Manage Nurse, where each one performs a specific function that helps meet the stated goal. Nowadays, the system is working perfectly.